Robert Bellah, religion og menneskelig evolution - Jensen, Hans J. Lundager (Religionsvidenskabeligt Tidsskrift, 2013)
ENGLISH ABSTRACT: Introduction to and discussion of Robert Bellah's major book, Religion in Human Evolution (2011). which defines and describes tribal religion (religion in pre-state societies), archaic religion (religion in early states) and religious currents in the axial age, the period in the middle of 1st mill. BC, where new radical and intellectual ideas and practices, sceptial or world renouncing, appeared in China, India and Greece. Hopefully, Bellah's book will be a standard reference work in the academic study of religion and an inspiration for the history of religion in the future to engage in historical and comparative studies. DANSK RESUMÉ: Introduktion til og diskussion af Robert Bellahs hovedværk fra 2011, Religion in Human Evolution, der definerer og beskriver tribal religion, dvs. religion i før-statslige samfund, arkaisk religion, dvs. religion i tidlig-statslige kulturer samt religiøse strømninger i aksetiden, perioden i midten af 1. årt. f.Kr., hvor nye radikale og intellektuelle, skeptiske eller verdensafvisende, tankegange og livsformer formuleres i Kina, Indien og Grækenland. Bogen bør betragtes som et hovedværk i aktuel religionsforskning, og den vil forhåbentlig kunne inspirere religionshistorien til også at drive historisk-komparativ forskning.